The Influence Of Digital Marketing And Product Quality On Thrifting Purchase Decisions At Toko Loka Lampung - Servicen, Servicen; Agus Purnomo (International Journal of Economics, Business and Innovation Research, 2025)
Evaluation of information technology with the internet in this digital era has now had an important impact at sundry vacet of exsistence, suchlike as the business sector. One of the most obvious impacts is the transformation in the way companies market their products and services through digital platforms, known as digital marketing. Apart from technological developments, lifestyle trends are also changing, one of which is the increasing popularity of thrifting or buying quality used goods. This study intend for analyse the effect digital marketing and product quality in thrifting purchase decisions at Toko Loka Lampung. Digital marketing as an independent variable includes social media, online promotions, and digital interactions, while product quality is measured through indicators of durability, design, and product conformity with consumer expectations. The purchasing decision which is the dependent variable are reviewed based on the desire to buy, frequency of purchase, and post-purchase satisfaction. This study utilize a quantitative method by an associative approach and the sample taken utilize a purposive sampling technique, consisting of Toko Loka Lampung consumers who have made purchases. Data was be gathered via questionnaires and analyzed utilize multiple linear regression. The results of this study are that X1 and X2 have an influence on Y.